Trypanosoma cruzi-induced immunosuppression: blockade of costimulatory T-cell responses in infected hosts due to defective T-cell receptor-CD3 functioning. - Lopes, M F (1994)
A model of experimental Trypanosoma cruzi murine infection with chemically induced metacyclic forms (opossum clone Dm28c) showed a marked state of T-cell unresponsiveness during acute phase, but lacked evidence of suppressor cell activity. Spleen cells from infected mice were suppressed in vitro in responses to T-cell activators concanavalin A, anti-Thy1 monoclonal antibody (MAb), and anti-CD3 MAb compared with spleen cells from control littermates. Activation with accessory cell-independent stimulus provided by immobilized anti-CD3 was defective in splenic CD4-positive T cells from infected mice, but not in such cells from control mice. No evidence of splenic suppressor cell activity was found in cell-mixing experiments using nylon-passed T cells from control and infected donors. Kinetic experiments showed that there was a discrete stage in infection when T cells were already suppressed in response to anti-CD3 but still responded to anti-CD69 MAb. In these T cells, immobilized anti-CD3 failed to enhance simultaneous CD69 responses, although anti-CD3 enhanced CD69 responses in control T cells from uninfected donors. These results demonstrate an intrinsic defect in T-cell receptor-mediated T-cell activation, which could be a mechanism generating T-cell suppression during infection by T. cruzi.